Prove by mathematical induction:

($\frac{a_{1} + ... + a_{n}}{n}$) $\geq \sqrt[\leftroot{0}\uproot{0}n]{a_{1}...a_{n}}$, where $n \in \mathbb{N}$.

So the base case: $n = 2$ means $\frac{a_{1} + a_{2}}{2} \geq a_{1}a_{2}$. Rearranging yields $(a_{1} - a_{2})^{2} \geq 0$.

The inductive step is where I am stuck at.

Any advice?


Let $$G = \sqrt[n]{x_1 \cdots x_{n}}$$ and it then follows that $x_1 \leq G \leq x_n$. Also $$x_1 +x_n \geq \frac{x_1x_n}{G}+G.$$

Implies $$\frac 1G (G-x_1)(x_n - G) \geq 0.$$

By Induction Hypothesis:

$$x_2 + \cdots +x_{n-1} + \frac{x_1x_n}{G} \geq (n-1)G$$ $\implies$ $$x_2 + \cdots +x_{n-1} + \frac{x_1x_n}{G} +G \geq nG$$ and use $x_1 +x_n \geq \frac{x_1x_n}{G}+G$ to get the reqd result.

  • $\begingroup$ You’re implicitly assuming $x_i$ are ordered (WLOG) and positive, probably worth stating. +1 $\endgroup$ – Macavity Oct 24 '17 at 4:44

The idea of the induction using can be the following.

For $n=2^k$, where $k$ is a natural number we can use AM-GM number times, like for $n=4$:

For non-negatives $a$, $b$, $c$ and $d$ we obtain:


Now, for $n=3$ we obtain: $$\frac{a+b+c+\sqrt[3]{abc}}{4}\geq\sqrt[4]{abc\sqrt[3]{abc}}=\sqrt[3]{abc},$$ which gives $$\frac{a+b+c}{3}\geq\sqrt[3]{abc}.$$

Or for non-negatives $a$, $b$, $c$, $d$ and $e$ we obtain: $$\frac{a+b+c+d+e+3\sqrt[5]{abcde}}{8}\geq\sqrt[8]{abcde\left(\sqrt[5]{abcde}\right)^3}=\sqrt[5]{abcde},$$ which gives $$\frac{a+b+c+d+e}{5}\geq\sqrt[5]{abcde}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.